Legal Features of Children's Rights and Duties During Armed Conflict: The Ukrainian Case - Chepkova, Kateryna (Review of European and Comparative Law, 2025)
It is universally recognized that children are the most vulnerable and unprotected category of civilians. Moreover, when it comes to the period of any armed conflict. The twientieth century is the Century of the Child. The international community’s actions, which were reflected in the adoption of a numer of international legal treaties establishing the legal status of the child in general and securing the rights of each child, are evidence of this. The rights of a child are one of the key elements of the legal construct of the legal status of a child. This article analyzes children’s rights both during the peaceful period and during the armed conflict. The article examines a numer of international legal treaties which enshrine children’s rights during armed conflict. Conventional wisdom does not refer to children’s duties. However, the period of armed conflict is fundamentally opposite to the peaceful period of the State’s existence. During an armed conflict, it is not alway spossible to fulfill children’s rights. On the contrary, this period is marked by increased risks to children’s lives and health. Moreover, it is necessary to take into account the nature og contemporary armed conflicts (their methods and means). Te period of armed conflict produces new rules of behawior (which may be restrictive) that are intended to maximize the life and health of each child. The behavioral rules form a numer of duties that are collective in nature (their fulfillment is entrusted to the children’s legal representatives, public administration bodies, and children themselves with due regard to their age). Based on the Ukrainian case study, the author analyzes a numer of duties arising during an armed conflict, and the fulfillment of which is entrusted to several actors, including children. During the course of writing the article, the author used the method of document analysis. First of all, the researcher analyzed international legal acts related to the topic of the study. The second level of legal acts that were analyzed were Ukrainian legal acts depending on their legal force. Simultaneously with the anaysis of regulatory acts, the author reviewed the academic literaturę that formed the scientific basis of this study. This helped to analyze the children’s rights and duties during armed conflicts. The scientific basis of the study is based on scientific publications in the field of children’s rights in general. The author used a systematic proces during the writing of the article, involving reading, identifying specific provisions, and categorizing information. The generalization method was applied on the basis of the comparison, which helped to formulate the relevant conclusions to the article.